Causal relationship between 14 site‐specific cancers and venous thromboembolism. Issue 4 (7th December 2022) - Chen, Xiong; Hong, Xiaosi; Luo, Shulu; Cai, Jiahao; Huang, Guiwu; Shen, Runnan; Lv, Lin; Bai, Gaochen; Fu, Wen; Yan, Li; Liu, Guochang; Huang, Kai; et al.
Abstract: Background: It has been observed that cancer and venous thromboembolism (VTE) are associated, but anticancer therapy may violate the causality. Therefore, this study aimed to elucidate the causal relationship of various cancers to VTE using Mendelian randomization (MR). Methods: Three MR methods were used to estimate causal effects: Inverse variance weighted (IVW), MR‐Egger and weighted median. Sensitivity analyses included Cochran's Q ‐test, MR‐Egger intercept test and MR‐PRESSO. Gene ontology enrichment analysis was performed to elucidate the underlying mechanisms of VTE development in cancer patients. Results: The primary IVW approach showed that non‐Hodgkin's lymphoma (NHL) might increase the risk of VTE (odds ratio [OR]: 1.20, 95% confidence interval [95% CI]: 1.00–1.44, p  = 0.045), while melanoma possibly reduced the risk of VTE (OR: 0.89, 95% CI: 0.82–0.97, p  = 0.006), although there was no significance after adjustment for multiple testing. No association was observed between VTE risk and other site‐specific cancers. Gene ontology enrichment analysis revealed that vitamin D played an important role in the development of VTE in cancer patients. Conclusions: Our findings suggested that genetically predicted NHL was associated with higher VTE risk, whereas melanoma had lower VTE risk compared with other site‐specific cancers. Moreover, this study suggested that anticancer therapy and increased extensive examination might play a more important role in VTE development than the nature of cancer. Abstract : Using Mendelian randomization study, we elucidated the causal effect between 14 site‐specific cancers and venous thromboembolism. Non‐Hodgkin's lymphoma increases risk of venous thromboembolism while melanoma decreases its risk. footnotes: VTE: venous thromboembolism; some icons were referenced from the Biorender (https://biorender.com/ ).